Clinical signs and post-mortem lesions caused by clostridial enterotoxemia in rabbits - A. S. Metleva; M. N. Khakimzyanova; E. E. Sionikhin (Ветеринария сегодня)
Enterotoxemia, accompanied by diarrhea and bloating, is still a matter of pressing concern to the rabbit farming. Clostridia bacteria are often isolated from the internal organs of rabbits that have died of an anaerobic infection. Clostridial infection, manifested in various forms, is a major problem for veterinarians. The following drivers contribute to the emergence of the infectious disease: malnutrition (insufficient fiber intake); non-compliance with hygiene requirements for animal handling; unsustainable use of antibacterial drugs; gastrointestinal congestion. All these drivers can disrupt healthy caecum microflora due to changes in the gastrointestinal environment. Low-fiber diets result in slow cecum motility, thus, delaying transit of the intestinal contents and eventually changing the microflora. Use of antibiotics together with stress make Clostridia accumulate in the gastrointestinal tract, at the same time, reducing the number of microorganisms of other groups. The first signs of toxicoinfection are observed when rabbit kits are weaned from does. Clinical manifestation begins with bloating, weakness, inappetence, which ultimately lead to death. Observations have shown that the risk group includes rabbit kits weaned from the 35–77-day old does. Mortality was less reported in breeding stock and among replacement young animals. Autopsy revealed signs of enterotoxemia: serous-catarrhal gastritis, serous-hemorrhagic lymphonodulitis, degenerated kidneys, liver and heart muscle; passive congestion of lungs and pulmonary edema. Microbiological diagnosis revealed Clostridium histolyticum and Clostridium perfringens species known for their pronounced toxigenic profile, most often bacteria were found in the stomach, intestines and heart.